A high-pressure-resistant in-situ polymerization polyurea electrolyte, a preparation method and application thereof

CN122889828APending Publication Date: 2026-10-09HUIZHOU MARATHON SOLID STATE NEW ENERGY BATTERY TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610850649.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-12
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]为解决高压下传统电解质稳定性差及离子迁移率低的问题,本发明的目的是提供一种耐高压原位聚合聚脲电解质的制备方法,具体包括以下步骤:

Benefits of technology

(1)本发明通过室温下引入不同的含二胺的扩链剂对聚(氨酯-脲)电解质的结构设计,实现对溶剂化结构的有效调控,同时,摒弃了传统PDMS惰性相与动态共价键,采用单一聚醚软段与永久性交联网络,结合高浓度锂盐配方(即空白电解质),有效解决了高压(>4.3V)下的溶胀变形风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889828A_ABST
    Figure CN122889828A_ABST
Patent Text Reader

Abstract

The application discloses a high-pressure-resistant in-situ polymerization polyurea electrolyte and a preparation method and application thereof, and belongs to the technical field of lithium metal batteries and electrolytes. Specifically, a crosslinking prepolymer is prepared by mixing a crosslinking agent ethylenediamine polyether tetrol and a polyether polyol; an isocyanate electrolyte is prepared by mixing dimethyl carbonate, ethylene carbonate, lithium hexafluorophosphate, fluoroethylene carbonate and hexamethylene diisocyanate trimer; a chain extender is added to the isocyanate electrolyte, and the crosslinking prepolymer is obtained to obtain an in-situ polymerization precursor; the in-situ polymerization precursor is assembled into a battery, and is cured to obtain the high-pressure-resistant in-situ polymerization polyurea electrolyte. The application regulates a poly (urethane-urea) solvation structure through the chain extender, and inhibits high-pressure swelling by combining polyether permanent crosslinking and high-concentration lithium salt. The electrolyte can generate an interface film containing LiF and a positive electrode polyamide protective layer in-situ at the positive and negative electrodes, inhibits lithium dendrites, improves pressure resistance, and realizes long-cycle stability of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium metal battery and electrolyte technology, specifically to a high-voltage resistant in-situ polymerized polyurea electrolyte, its preparation method, and its application. Background Technology

[0002] Traditional carbonate electrolytes pose a risk of catastrophic safety accidents such as thermal runaway, fire, and explosion. Furthermore, their fundamental deficiency at high voltages stems from the electronic structure of the solvent molecules themselves. Cyclic carbonates (such as EC and FEC) and linear carbonates (such as DMC) have higher highest occupied molecular orbital energy levels, leading to potential problems when the battery is charged to high voltages (>4.3 V vs. Li / Li). + When the solvent loses electrons at the positive electrode surface, reactions such as oxidation, dehydrogenation, and ring-opening occur. These decomposition products not only damage the integrity of the cathode electrolyte interphase (CEI), but the reactive oxygen species and protons released during oxidation also accelerate the dissolution of the cathode transition metal and structural collapse. Furthermore, excessive electrolyte consumption can trigger side reactions at the interface, resulting in a fragile solid electrolyte interphase (SEI) structure that is prone to "dead lithium." These problems not only increase the safety risk of battery puncture but also severely affect the battery's cycle performance.

[0003] Existing polyurea / polyurethane gel electrolytes (such as CN116565307A) typically employ polyether polyols and polydimethylsiloxanes as dual soft segments, relying on polarity differences to achieve phase separation. However, in this system, polydimethylsiloxane is chemically inert, serving only as a physical reinforcing phase and unable to participate in electrochemical processes, resulting in high interfacial impedance and an inability to suppress oxidative decomposition under high voltage. More critically, existing networks generally lack electron-deficient characteristics, failing to regulate the electron cloud density of polymer polar groups through electronic effects. Consequently, their ability to control the lithium-ion solvation structure is insufficient, and they also cannot effectively promote the dissociation and reductive decomposition of anions, making it difficult to suppress interfacial side reactions and lithium dendrite growth under high voltage, severely limiting the performance of lithium metal batteries. Furthermore, some studies have attempted to introduce dynamic covalent bonds (such as disulfide bonds and borate ester bonds) to achieve recyclability, but this leads to insufficient crosslinking density, resulting in swelling deformation and internal short-circuit risks under high voltage (>4.3 V). Therefore, there is an urgent need to develop a novel electrolyte system that combines high pressure resistance, antioxidant properties, interfacial catalytic activity, and solvation regulation capabilities. Summary of the Invention

[0004] To address the problems of poor stability and low ion mobility of traditional electrolytes under high pressure, the present invention aims to provide a method for preparing a high-pressure resistant in-situ polymerized polyurea electrolyte, specifically including the following steps: S1 mixes the crosslinking agent ethylenediamine polyether tetraol and polyether polyol to obtain mixture 1; mixture 1 is degassed by vacuum stirring and dried to obtain crosslinked prepolymer.

[0005] S2 mixes dimethyl carbonate, ethylene carbonate, lithium hexafluorophosphate, and fluoroethylene carbonate to obtain an electrolyte; under a nitrogen atmosphere, hexamethylene diisocyanate trimer is added to the electrolyte and mixed evenly to obtain an isocyanate electrolyte.

[0006] In S3, under a nitrogen atmosphere, a chain extender is added to the isocyanate electrolyte and mixed evenly to obtain mixture 2; the crosslinked prepolymer is added dropwise to mixture 2 and mixed evenly to obtain the in-situ polymerization precursor.

[0007] S4 assembles the in-situ polymerized precursor into a battery, then cures it to obtain a high-voltage resistant in-situ polymerized polyurea electrolyte.

[0008] Preferably, in step S1 of the present invention, the molar ratio of the hydroxyl groups of ethylenediamine polyether tetraol to the hydroxyl groups of polyether polyol is 1:(2.1~3).

[0009] Preferably, the vacuum stirring and degassing time in step S1 of the present invention is 25-30 minutes.

[0010] Preferably, the drying conditions in step S1 of the present invention are: vacuum drying at 60~80°C for 2~6 hours.

[0011] Preferably, in step S2 of the present invention, the mass ratio of dimethyl carbonate, ethylene carbonate, lithium hexafluorophosphate and fluoroethylene carbonate is (55~65):(15~25):(15~20):(1~5).

[0012] Preferably, the chain extender in step S3 of the present invention is 5,6-diaminobenzimidazole or diethyltoluenediamine.

[0013] Preferably, the molar ratio of the primary amine group in the chain extender, the hydroxyl group in the crosslinked prepolymer, and the isocyanate group in the isocyanate electrolyte of the present invention is 1:(4.5~5.0):(5.9~6.0).

[0014] Preferably, the curing conditions in step S4 of the present invention are: standing at 25~30°C for 20~36 hours.

[0015] Another object of the present invention is to provide a high-pressure resistant in-situ polymerized polyurea electrolyte prepared by the method described in the present invention.

[0016] Another objective of this invention is to provide an application of a high-voltage resistant in-situ polymerized polyurea electrolyte in lithium batteries.

[0017] This invention provides a high-pressure resistant in-situ polymerized polyurea electrolyte, its preparation method, and its application, which have the following beneficial effects: (1) This invention achieves effective control of the solvation structure by introducing different diamine-containing chain extenders to the structure design of poly(urethane-urea) electrolyte at room temperature. At the same time, it abandons the traditional PDMS inert phase and dynamic covalent bond, adopts a single polyether soft segment and permanent cross-linking network, combined with a high-concentration lithium salt formulation (i.e. blank electrolyte), effectively solving the risk of swelling and deformation under high voltage (>4.3V).

[0018] (2) The present invention promotes the in-situ growth of a lithium fluoride (LiF)-rich SEI film on the surface of lithium metal at the negative electrode interface. This film can promote the uniform deposition of lithium ions and effectively reduce the risk of lithium dendrite puncture, thereby improving the interface stability between the electrolyte and the lithium metal negative electrode. A polyacrylamide compound (polyamide protective layer) and a LiF-rich interface layer are formed in-situ on the CEI at the positive electrode interface. This significantly improves the battery's tolerance performance under high voltage, addressing the problem of electrolyte decomposition under high voltage.

[0019] (3) Through structural design, interface control and the synergistic effect of each raw material, the present invention increases the lithium-ion transference number to more than 0.75 and achieves stable cycling of lithium metal batteries for more than 1,000 hours at 30°C and excellent rate performance, thereby comprehensively improving the interface stability, safety and cycle life of the battery. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the in-situ construction method of high-pressure resistant polyurea electrolyte according to Embodiment 1 of the present invention.

[0021] Figure 2 This is an X-ray photoelectron spectrum (fluorine spectrum) of the high-voltage resistant polyurea electrolyte of Embodiment 1 of the present invention on the lithium surface after cycling.

[0022] Figure 3 This is a comparison chart of ion transport numbers between the high-voltage resistant polyurea electrolyte and the blank electrolyte in Example 1 of the present invention. Figure 3 (a) is the ion transport number diagram of the blank electrolyte. Figure 3 (b) is the ion transport number diagram of the high-voltage resistant polyurea electrolyte.

[0023] Figure 4 This is a comparison chart of the long cycle times of lithium symmetric batteries using high-voltage resistant polyurea electrolyte and blank electrolyte in Example 1 of this invention.

[0024] Figure 5This is a distribution diagram of the electrostatic potential (ESP) of the high-voltage resistant polyurea electrolyte in Embodiment 1 of the present invention.

[0025] Figure 6 This is an XPS comparison image of the CEI on the surface of the 811 cathode after high-voltage cycling of the high-voltage resistant polyurea electrolyte of Example 1 of the present invention and the blank electrolyte. Figure 6 (a) is the nitrogen spectrum. Figure 6 (b) is the fluorine spectrum.

[0026] Figure 7 This is a comparison chart of the number of full-cell cycles of the high-voltage resistant polyurea electrolyte and the blank electrolyte in Example 1 of the present invention.

[0027] Figure 8 This is the Raman spectrum of the high-voltage resistant polyurea electrolyte and the blank electrolyte control group in Example 1 of the present invention.

[0028] Figure 9 This is the X-ray photoelectron spectrum (fluorine spectrum) of the high-voltage resistant polyurea electrolyte on the lithium surface after cycling, as shown in Example 2 of this invention.

[0029] Figure 10 This is a comparison chart of ion transport numbers between the high-voltage resistant polyurea electrolyte and the blank electrolyte in Example 2 of the present invention. Figure 10 (a) is the ion transport number diagram of the blank electrolyte. Figure 10 (b) is the ion transport number diagram of the high-voltage resistant polyurea electrolyte.

[0030] Figure 11 This is a comparison chart of the long cycle times of lithium symmetric batteries using high-voltage resistant polyurea electrolyte and blank electrolyte in Example 2 of this invention.

[0031] Figure 12 This is a comparison chart of the number of full-cell cycles of the high-voltage resistant polyurea electrolyte and the blank electrolyte in Example 2 of this invention. Detailed Implementation

[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] The crosslinking agent ethylenediamine polyether tetraol (N403) in this invention has the following structural formula: ; The structural formula of the polyether polyol (TMN3000, Mn=3000) is as follows: ; The structural formula of hexamethylene diisocyanate trimer (HDI trimer) is as follows: ; The structural formula of the chain extender 5,6-diaminobenzimidazole one (5,6-DABI) is as follows: ; The structural formula of diethyltoluenediamine (E100) is as follows: .

[0034] Example 1 A method for preparing a high-pressure resistant in-situ polymerized polyurea electrolyte containing 5,6-DABI specifically includes the following steps: S1. Ethylenediamine polyether tetraol (N403), a crosslinking agent containing tetrahydroxyl groups, and soft-chain polyether polyol (TMN3000, Mn=3000), containing trihydroxyl groups, are mixed at a hydroxyl molar ratio of 1:2.2 to obtain mixture 1. The mixture is stirred at 500 rpm for 30 minutes in a vacuum degassing machine, and then placed in a vacuum oven at 80℃ for 2 hours to remove trace amounts of hygroscopic moisture, thus obtaining the crosslinked prepolymer for later use.

[0035] S2. Dimethyl carbonate (DMC), ethylene carbonate (EC), lithium hexafluorophosphate (LiPF6), and fluoroethylene carbonate (FEC) are mixed (the mass ratio of DMC, ethylene carbonate, lithium hexafluorophosphate, and fluoroethylene carbonate is 59.5:19.8:18.2:2.5) to obtain an electrolyte. In a glove box under nitrogen protection (at room temperature), a white viscous liquid hexamethylene diisocyanate trimer (HDI trimer) is added to the electrolyte. The mixture is magnetically stirred for 30 minutes until the HDI trimer is completely dissolved and mixed evenly to obtain a homogeneous isocyanate electrolyte solution for later use.

[0036] In an inert gas atmosphere, the isocyanate electrolyte solution was placed on a magnetic stirrer, and the chain extender 5,6-diaminobenzimidazole one (5,6-DABI) was added to the isocyanate electrolyte solution. The mixture was stirred until completely dispersed to obtain mixture 2 (the molar ratio of primary amine groups in 5,6-DABI, hydroxyl groups in the crosslinked prepolymer, and isocyanate groups in the isocyanate electrolyte was 1:4.8:5.9). The crosslinked prepolymer was slowly added dropwise to mixture 2, and the mixture was stirred vigorously for 1 minute to obtain a liquid transparent in-situ polymerization precursor.

[0037] S4 adds the in-situ polymerization precursor to the positive electrode surface and both sides of the separator of the lithium-ion battery to ensure complete wetting; after assembling into a soft-pack battery, it is placed in a 30°C constant temperature oven and left to stand for 24 hours; the isocyanate groups (-NCO) react with the amino / hydroxyl groups to form a polyurea electrolyte network containing benzene ring chain extender in situ.

[0038] The chemical structure of the above-mentioned network polymer is shown below: .

[0039] The electrolyte of this embodiment is assembled into a lithium-to-lithium battery, and after cycling, the following results are obtained: Figure 2 The X-ray photoelectron spectroscopy (fluorine spectrum) shown, compared with the blank electrolyte, reveals a significant increase in the intensity of the characteristic peak of LiF in the SEI film after the introduction of DABI. This confirms that the electron-deficient benzene ring catalyzes PF6 through an electron deprivation effect. - The reduction and decomposition process constructs a stable SEI membrane rich in inorganic components.

[0040] The comparison of ion transport numbers between the electrolyte prepared in this embodiment and the blank electrolyte is shown in the figure below. Figure 3 As shown, the lithium-ion transference number (t) of the electrolyte in the DABI system of this embodiment is... + The efficiency reached 0.75, which is much higher than that of the blank control group (about 0.4), indicating that the DABI system improves the lithium-ion transport efficiency.

[0041] The comparison of long-cycle times of lithium-symmetric batteries using the electrolyte prepared in this embodiment and the blank electrolyte is shown in the figure below. Figure 4 As shown, at 1mAh / cm 2 At a current density of 1000 ohms, the DABI system achieved dendrite-free stable cycling for over 1000 hours with extremely low overpotential, which directly proves the effective suppression of lithium dendrites by the LiF / Li3N SEI film.

[0042] In the electrolyte prepared in this embodiment, the 5,6-DABI chain extender and PF6 - The electrostatic potential (ESP) distribution diagram of the interaction, where the blue area represents electron-deficient centers, demonstrates the strong electron-withdrawing properties of the 5,6-DABI framework. This confirms that the polymer network can strongly anchor lithium salt anions through anion-π interactions, providing direct microscopic evidence for the "electron deprivation catalysis mechanism".

[0043] The electrolyte of this embodiment was assembled into an NCM811 full cell. After 50 cycles, the positive electrode was removed and its surface was analyzed by X-ray photoelectron spectroscopy. The DABI system not only detected a high content of LiF (…) in the CEI… Figure 6 In (b), a distinct characteristic peak of polyamide compounds appeared at ~398.5 eV. Figure 6 (a) This confirms that DABI underwent in-situ polymerization at the positive electrode interface under high pressure, constructing a high-pressure resistant organic-inorganic composite protective layer.

[0044] The electrolyte of this embodiment was assembled into a high-load NCM523 full cell. The DABI system achieved a rate of 19 mg / cm³ at 0.2C.2 After 200 cycles, the capacity retention exceeds 90% (e.g. Figure 7 The results showed that the electrolyte system was significantly better than the control group, which verified the excellent application prospects of the electrolyte system under actual high pressure.

[0045] The Raman spectra of the electrolyte prepared in this embodiment and the blank electrolyte are as follows: Figure 8 As shown, the DABI-containing system promoted the formation of ion-pair solvated structures in the polymerized polyurea backbone compared to the control group, confirming its favorable effect on the formation of lithium fluoride-rich SEIs.

[0046] Example 2 A method for preparing a high-voltage resistant in-situ polymerized polyurea electrolyte containing E100 specifically includes the following steps: S1. Ethylenediamine polyether tetraol (N403), a crosslinking agent containing tetrahydroxyl groups, and soft-chain polyether polyol (TMN3000, Mn=3000), containing trihydroxyl groups, are mixed at a hydroxyl molar ratio of 1:2.2 to obtain mixture 1. The mixture is stirred at 500 rpm for 30 minutes in a vacuum degassing machine, and then placed in a vacuum oven at 80℃ for 2 hours to remove trace amounts of hygroscopic moisture, thus obtaining the crosslinked prepolymer for later use.

[0047] S2. Dimethyl carbonate (DMC), ethylene carbonate (EC), lithium hexafluorophosphate (LiPF6), and fluoroethylene carbonate (FEC) are mixed (the mass ratio of DMC, ethylene carbonate, lithium hexafluorophosphate, and fluoroethylene carbonate is 59.5:19.8:18.2:2.5) to obtain an electrolyte. In a glove box under nitrogen protection (at room temperature), a white viscous liquid hexamethylene diisocyanate trimer (HDI trimer) is added to the electrolyte. The mixture is magnetically stirred for 30 minutes until the HDI trimer is completely dissolved and mixed evenly to obtain a homogeneous isocyanate electrolyte solution for later use.

[0048] In an inert gas atmosphere, the isocyanate electrolyte solution was placed on a magnetic stirrer, and the chain extender diethyltoluenediamine (E100) was added to the isocyanate electrolyte solution. The mixture was stirred until it was completely dispersed to obtain mixture 2 (the molar ratio of primary amine groups in E100, hydroxyl groups in the crosslinked prepolymer, and isocyanate groups in the isocyanate electrolyte was 1:4.8:5.9). The crosslinked prepolymer was slowly added dropwise to mixture 2, and the mixture was stirred vigorously for 1 minute to mix evenly, thus obtaining a liquid transparent in-situ polymerization precursor.

[0049] S4 adds the in-situ polymerization precursor to the positive electrode surface and both sides of the separator of the lithium-ion battery to ensure complete wetting; after assembling into CR2025 button cells or pouch cells, it is placed in a 30°C constant temperature oven and left to stand for 20 hours; the isocyanate groups (-NCO) react with the amino / hydroxyl groups to form a polyurea electrolyte network containing benzene ring chain extenders in situ.

[0050] The chemical structure of the above-mentioned network polymer is shown below: .

[0051] The X-ray photoelectron spectroscopy (fluorine spectrum) of the polyurea electrolyte containing E100 chain extender prepared in this embodiment and the blank electrolyte on the lithium surface after cycling is shown in the figure below. Figure 9 The highest level of lithium fluoride was found in the SEI of the lithium metal anode of the polyurea electrolyte containing E100 chain extender.

[0052] The comparison of ion transport numbers between the electrolyte prepared in this embodiment and the blank electrolyte is shown in the figure below. Figure 10 As shown, the lithium-ion transference number (t) of the E100 system in this embodiment is... + The value reached 0.69, which was much higher than that of the blank control group (approximately 0.4).

[0053] The comparison of long-cycle times of lithium-symmetric batteries using the electrolyte prepared in this embodiment and the blank electrolyte is shown in the figure below. Figure 11 As shown, at 1mAh / cm 2 At current densities, the E100 system achieved stable cycling for over 800 hours.

[0054] The electrolyte of this embodiment was assembled into a high-load NCM523 full cell, and the polyurea electrolyte battery containing E100 chain extender was found to be able to cycle stably for more than 190 times.

[0055] Example 3 A method for preparing a high-pressure resistant in-situ polymerized polyurea electrolyte containing 5,6-DABI specifically includes the following steps: S1. Ethylenediamine polyether tetraol (N403), a crosslinking agent containing tetrahydroxyl groups, and soft chain polyether polyol (TMN3000, Mn=3000), containing trihydroxyl groups, are mixed at a hydroxyl molar ratio of 1:2.5 to obtain mixture 1. The mixture is stirred at 500 rpm for 20 minutes in a vacuum degassing machine, and then placed in a vacuum oven at 60℃ for 3 hours to remove trace amounts of hygroscopic moisture, thus obtaining the crosslinked prepolymer for later use.

[0056] S2. Dimethyl carbonate (DMC), ethylene carbonate (EC), lithium hexafluorophosphate (LiPF6), and fluoroethylene carbonate (FEC) are mixed (the mass ratio of DMC, ethylene carbonate, lithium hexafluorophosphate, and fluoroethylene carbonate is 55:15:15:5) to obtain an electrolyte. In a glove box under nitrogen protection (room temperature), a white viscous liquid hexamethylene diisocyanate trimer (HDI trimer) is added to the electrolyte. The mixture is magnetically stirred for 30 minutes until the HDI trimer is completely dissolved and mixed evenly to obtain a homogeneous isocyanate electrolyte solution for later use.

[0057] In an inert gas atmosphere, the isocyanate electrolyte solution was placed on a magnetic stirrer, and the chain extender 5,6-diaminobenzimidazole one (5,6-DABI) was added to the isocyanate electrolyte solution. The mixture was stirred until completely dispersed to obtain mixture 2 (the molar ratio of primary amine groups in 5,6-DABI, hydroxyl groups in the crosslinked prepolymer, and isocyanate groups in the isocyanate electrolyte was 1:4.5:5.9). The crosslinked prepolymer was slowly added dropwise to mixture 2, and the mixture was stirred vigorously for 1 minute to obtain a liquid transparent in-situ polymerization precursor.

[0058] S4 adds the in-situ polymerization precursor to the positive electrode surface and both sides of the separator of the lithium-ion battery to ensure complete wetting; after assembling into a soft-pack battery, it is placed in a constant temperature oven at 25°C and left to stand for 36 hours; the isocyanate groups (-NCO) react with the amino / hydroxyl groups to form a polyurea electrolyte network containing benzene ring chain extender in situ.

[0059] Performance: The prepared electrolyte has a performance of 1 mAh / cm³. 2 At a current density of 1 mAh / cm³, the DABI system achieved stable cycling for over 900 hours. In this embodiment, the electrolyte is at 1 mAh / cm³. 2 Lithium-ion transference number (t) at current density + The value reached 0.71.

[0060] Example 4 A method for preparing a high-pressure resistant in-situ polymerized polyurea electrolyte containing 5,6-DABI specifically includes the following steps: S1. Ethylenediamine polyether tetraol (N403), a crosslinking agent containing tetrahydroxyl groups, and soft chain polyether polyol (TMN3000, Mn=3000), containing trihydroxyl groups, are mixed at a hydroxyl molar ratio of 1:3 to obtain mixture 1. The mixture is stirred at 500 rpm for 60 minutes in a vacuum degassing machine, and then placed in a vacuum oven at 90°C for 1 hour to remove trace amounts of hygroscopic moisture, thus obtaining the crosslinked prepolymer for later use.

[0061] S2 mixes dimethyl carbonate (DMC), ethylene carbonate (EC), lithium hexafluorophosphate (LiPF6), and fluoroethylene carbonate (FEC) in a mass ratio of 65:25:25:1 to obtain an electrolyte. In a nitrogen-protected glove box (room temperature), a white viscous liquid hexamethylene diisocyanate trimer (HDI trimer) is added to the electrolyte. The mixture is then magnetically stirred for 30 minutes until the HDI trimer is completely dissolved and homogeneous, resulting in a uniform isocyanate electrolyte solution for later use.

[0062] In an inert gas atmosphere, the isocyanate electrolyte solution was placed on a magnetic stirrer, and the chain extender 5,6-diaminobenzimidazole one (5,6-DABI) was added to the isocyanate electrolyte solution. The mixture was stirred until it was completely dispersed to obtain mixture 2 (the molar ratio of primary amine groups in 5,6-DABI, hydroxyl groups in the crosslinked prepolymer, and isocyanate groups in the isocyanate electrolyte was 1:5:6). The crosslinked prepolymer was slowly added dropwise to mixture 2, and the mixture was stirred vigorously for 1 minute to obtain a liquid transparent in-situ polymerization precursor.

[0063] S4 adds the in-situ polymerization precursor to the positive electrode surface and both sides of the separator of the lithium-ion battery to ensure complete wetting; after assembling into a soft-pack battery, it is placed in a 30°C constant temperature oven and left to stand for 20 hours; the isocyanate groups (-NCO) react with the amino / hydroxyl groups to form a polyurea electrolyte network containing benzene ring chain extender in situ.

[0064] Performance: The prepared electrolyte has a performance of 1 mAh / cm³. 2 At a current density of [value missing], the DABI system achieved stable cycling for over 840 hours. In this embodiment, the electrolyte [value missing] mAh / cm³ [value missing]. 2 Lithium-ion transference number (t) at current density + The value reached 0.73.

[0065] Comparative Example 1 To prepare a blank electrolyte, dimethyl carbonate (DMC), ethylene carbonate (EC), lithium hexafluorophosphate (LiPF6), and fluoroethylene carbonate (FEC) were mixed (the mass ratio of dimethyl carbonate, ethylene carbonate, lithium hexafluorophosphate, and fluoroethylene carbonate was 59.5:19.8:18.2:2.5) to obtain the blank electrolyte.

[0066] In summary, this invention uses trihydroxy polyether, tetrahydroxy crosslinking agent, HDI trimer, and high-lithium salt electrolyte as raw materials to form an in-situ crosslinked film inside the battery, removing inert components and dynamic covalent bonds of PDMS and suppressing high-voltage swelling. Two aromatic diamine chain extenders, 5,6-DABI and diethyltoluene diamine (E100), are selected respectively: 5,6-DABI reconstructs Li through a strong electron-withdrawing framework. + Solvation structure, catalysis of PF6 - The decomposition process generates a LiF-containing composite interface film in situ at both the positive and negative electrodes, achieving a lithium-ion migration number of 0.75 and over 1000 hours of cycling in lithium-symmetric batteries. E100, by providing a rigid framework, optimizes the electrochemical stability window, achieving a migration number of 0.69 and over 800 hours of cycling. This electrolyte is suitable for high-voltage lithium metal batteries, effectively suppressing lithium dendrite formation and significantly improving the overall battery cycle stability.

[0067] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-pressure resistant in-situ polymerized polyurea electrolyte, characterized in that, Specifically, the following steps are included: S1. Crosslinking agent ethylenediamine polyether tetraol and polyether polyol are mixed to obtain mixture 1; mixture 1 is degassed by vacuum stirring and dried to obtain crosslinked prepolymer; S2 mixes dimethyl carbonate, ethylene carbonate, lithium hexafluorophosphate and fluoroethylene carbonate to obtain an electrolyte; under an inert gas atmosphere, hexamethylene diisocyanate trimer is added to the electrolyte and mixed evenly to obtain an isocyanate electrolyte; S3 In an inert gas atmosphere, a chain extender is added to the isocyanate electrolyte and mixed evenly to obtain mixture 2; the crosslinked prepolymer is added dropwise to mixture 2 and mixed evenly to obtain the in-situ polymerization precursor; S4 assembles the in-situ polymerized precursor into a battery, then cures it to obtain a high-voltage resistant in-situ polymerized polyurea electrolyte.

2. The method for preparing high-pressure resistant in-situ polymerized polyurea electrolyte according to claim 1, characterized in that, The molar ratio of the hydroxyl groups of the ethylenediamine polyether tetraol and the hydroxyl groups of the polyether polyol in step S1 is 1:(2.1~3).

3. The method for preparing high-pressure resistant in-situ polymerized polyurea electrolyte according to claim 1, characterized in that, The vacuum stirring and degassing time in step S1 is 20-60 minutes.

4. The method for preparing high-pressure resistant in-situ polymerized polyurea electrolyte according to claim 1, characterized in that, The drying conditions described in step S1 are: vacuum drying at 60~90℃ for 1~3 hours.

5. The method for preparing high-pressure resistant in-situ polymerized polyurea electrolyte according to claim 1, characterized in that, In step S2, the mass ratio of dimethyl carbonate, ethylene carbonate, lithium hexafluorophosphate, and fluoroethylene carbonate is (55~65):(15~25):(15~20):(1~5).

6. The method for preparing high-pressure resistant in-situ polymerized polyurea electrolyte according to claim 1, characterized in that, The chain extender mentioned in step S3 is 5,6-diaminobenzimidazole or diethyltoluenediamine.

7. The method for preparing high-pressure resistant in-situ polymerized polyurea electrolyte according to claim 1, characterized in that, The molar ratio of the primary amine group in the chain extender, the hydroxyl group in the crosslinked prepolymer, and the isocyanate group in the isocyanate electrolyte is 1:(4.5~5.0):(5.9~6.0).

8. The method for preparing high-pressure resistant in-situ polymerized polyurea electrolyte according to claim 1, characterized in that, The curing conditions described in step S4 are: standing at 25~30℃ for 20~36 hours.

9. A high-pressure resistant in-situ polymerized polyurea electrolyte prepared by the method according to any one of claims 1 to 8.

10. The application of the high-voltage resistant in-situ polymerized polyurea electrolyte as described in claim 9 in lithium batteries.

Citation Information

Patent Citations

  • Polyurea and / or polyurethane-based gel electrolyte as well as preparation method and application thereof

    CN116565307A